Study on parameters characteristics of DDGM(1, 1) prediction model with multiplication transformation. Issue 3 (26th June 2018) - Cui, Jie; Ma, Hongyan
Abstract : Purpose: The purpose of this paper is to reveal the changing role of the parameters of the DDGM(1, 1) model after multiple transformations in the modeling sequence. Design/methodology/approach: This paper considers DDGM(1, 1) model as the research object, adopts the parameter packet technique to analyze the influence of multiple transformations on the modeling accuracy of this model and discusses the quantitative relation of model parameters as multiple transformations in system's characteristic sequences. Findings: The results of numerical calculation show that the modeling accuracy of DDGM(1, 1) model is not affected by multiple transformations in the characteristics sequence of systems. Originality/value: The paper succeeds in realizing the properties of DDGM(1, 1) model by using the method of multiple transformations, which is helpful to understand the modeling mechanism and expand the application range of DDGM(1, 1) model.